Interface control of tetragonal ferroelectric phase in ultrathin Si-doped HfO2 epitaxial films. (1st April 2021) - Li, Tao; Dong, Juncai; Zhang, Nian; Wen, Zicheng; Sun, Zhenzhong; Hai, Yang; Wang, Kewei; Liu, Huanyu; Tamura, Nobumichi; Mi, Shaobo; Cheng, Shaodong; Ma, Chuansheng; et al.
Abstract: Nanoscaled HfO2 -based ferroelectric thin films are a favored candidate for the integration of next-generation memory and logic devices. The unique advantage is that the ferroelectric polarization becomes more robust than the traditional perovskite ferroelectrics when the size is reduced. Understanding and controlling the ferroelectricity requires high-quality epitaxial thin films to explore intrinsic ferroelectric mechanism and evaluate device applications. Here, we report a semicoherent growth of ITO as a bottom electrode that enables genuine ultrathin epitaxial films of Si-doped HfO2 on YSZ[001]/[110]/[111] substrates. The deposited films, which are under epitaxial compressive strain, display large ferroelectric polarization values up to 42 μC/cm 2 and do not need wake-up cycling. Structural characterization reveals the presence of crystalline domains with short axes of the tetragonal structure oriented perpendicular to the substrate. Using piezoforce microscopy, polar domains can be written and read and can be reversibly switched with a phase change of 180 o . Ferroelectric polarization can be controlled by ITO surface polarity which can easily exploit the interfacial valance mismatch to influence the electrostatic potential across the interface. These findings have implications for our understanding of ferroelectric switching and offer easy method to manipulate domain reversal state in HfO2 -based ferroelectric materials. Graphical abstract: Image, graphical abstract